A CROSS - SECTIONAL QUESTIONNAIRE BASED STUDY ON LEARNING STYLES AMONG UNDERGRADUATE MEDICAL STUDENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Medical education demands rapid adaptation to complex curricula, making the understanding of individual learning styles crucial for optimizing student performance. The VARK model (Visual, Aural, Read/Write, Kinesthetic) provides a framework to assess these preferences, yet studies on medical undergraduates remain limited. This study aimed to identify the preferred sensory modalities for learning and explore potential differences across gender and academic years. Methods: A cross-sectional study was conducted among third- and final-year medical students using the pre-validated VARK questionnaire (Version 8.0). The questionnaire assessed preferences for unimodal (single style) or multimodal (combined styles) learning. Data were analyzed to determine associations between learning styles, gender, and year of study using chi-square tests. (SPSS version 20.0, p